Implementasi Metode AHP dalam Menentukan Penerima Beasiswa Komite Sekolah - Asnawati Asnawati; Prahasti Prahasti; Liza Yulianti (STMIK Budi Darma, 2021)
Award for an outstanding student by the school through the school committee needs to be given in an effort to increase student motivation and enthusiasm for learning. Through the awarding of committee money exemption scholarships, students are expected to continue to improve their performance. Students who receive school committee scholarships are the best students who are judged based on certain criteria. The criteria for scholarship recipients have been determined by SMKN 2 Bengkulu City, however, the selection is still using a manual system. The use of this system has constraints in that it takes a long time to manage. In addition, subjectivity was still found in the assessment. A better alternative system is needed in the management of school committee scholarship recipients. The use of the Analytical Hierarchy Process (AHP) method in the Decision Support System (SPK) will give the best results so that students who really deserve scholarships will be obtained. The Decision Support System at SMKN 2 Bengkulu City in determining recipients of school committee scholarships is based on criteria, namely report card scores, academic achievement and non-academic achievements with a predetermined weighting rating. The results of the calculation obtained the final value based on rank one to three obtained values of 0.3925, 0.2150 and rank 3 with a final value of 0.1434. Based on the results of the existing ranking, it has produced scholarship recipients who actually meet the predetermined criteria